PENGETAHUAN IBU TENTANG VITAMIN A PADA BALITA DI POSYANDU MELATI I KADIPIRO SURAKARTA - Darah Ifalahma (OVUM : Journal of Midwifery and Health Sciences, 2021)
Vitamin A is an important nutrient for toddlers to prevent blindness, as a survival, health and growth of children. In Indonesia, giving high doses of vitamin A is very important to overcome the problem of vitamin A deficiency (VAC). Preliminary study at Posyandu Melati I Kadipiro of 15 respondents 3 mothers knew about vitamin A, 5 mothers only knew about vitamin A and 7 mothers did not know about vitamin A. This study aims to determine mother's knowledge about vitamin A in toddlers at Posyandu Melati I Kadipiro. The design of this study uses a quantitative descriptive method. The samples is all mothers who have toddlers at Posyandu Melati I Kadipiro obtained 62 respondents with non-probability sampling technique by means of saturated samples. Research instruments using closed questionnaires. Univariate analysis with frequency distribution. The results obtained from the knowledge of mothers about vitamin A in infants at Posyandu Melati I Kadipiro in the good category, namely as many as 14 mothers (22.58%), sufficient category as many as 32 mothers (51.61%), and less categories as many as 16 mothers ( 25.81%). The conclusion from this research is that the mother's knowledge of vitamin A in children under five at the Posyandu Melati I Kadipiro is in the sufficient category.